IDENTIFICATION OF MACROPHYTA IN THE SWAMP AREA OF THE SAWAH VILLAGE, KAMPAR REGENCY, RIAU PROVINCE - Nasution, Aprilia Safitri; Windarti, Windarti; Efawani, Efawani (Asian Journal of Aquatic Sciences, 2019)
There were many types of macrophyta present in the swamp area of the Sawah Village, but there was no information about the types of macrophyta in that area. To understand the type of macrophyta presence in that area, a research has been carried out in February 2019. The method usedz is a the survey method, where the swanp area of the Sawah Village used as the location of the research and macrophytes as the object of research. Sampling was done once during the study. The plants were then identified based on Steenis (1981). There are 10 types of macrophytes found in the swanp area of the Sawah Village namely: Colocasia esculenta, Eichhornia crassipes, Eleocharis dulcis, Paspalum comersonii, Azolla pinnata, Utricularia aurea, Salvinia natans, Nepbrolepis biserrata, Monochoria vaginalis, Panicum repens